2013
DOI: 10.3390/ijerph10083217
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Social Ecological Contributors to Diabetes within Hispanics in an Underserved U.S.-Mexico Border Community

Abstract: Hispanics bear a disproportionate burden of diabetes in the United States, yet relations of structural, socio-cultural and behavioral factors linked to diabetes are not fully understood across all of their communities. The current study examines disparities and factors associated with diabetes in adult Hispanics of Mexican-descent (N = 648) participating in a population survey of an underserved rural U.S.-Mexico border community. The overall rate of diabetes prevalence rate in the sample, based on self-report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 35 publications
0
23
1
2
Order By: Relevance
“…Additionally, Mexican Americans residing in rural or unincorporated areas show higher rates of diabetes and associated comorbidities when compared to non-Hispanic Whites or Mexican Americans living in other U.S. regions (Anders et al, 2008; Balcazar et al, 2010; Koopman, Mainous, & Geesey, 2006). One study reported the diabetes prevalence among Hispanic residents in U.S.–Mexico border communities was over 20% (Chang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Mexican Americans residing in rural or unincorporated areas show higher rates of diabetes and associated comorbidities when compared to non-Hispanic Whites or Mexican Americans living in other U.S. regions (Anders et al, 2008; Balcazar et al, 2010; Koopman, Mainous, & Geesey, 2006). One study reported the diabetes prevalence among Hispanic residents in U.S.–Mexico border communities was over 20% (Chang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the majority of participants who self-reported, they exercised and recognizing that BMI is directly influenced by the balance between caloric intake and physical activity, these were not the expected BMI results. Of note is the proportion who self-reported they exercised is greater than other border studies ( 4 , 23 , 24 ). The MX–U.S.…”
Section: Discussionmentioning
confidence: 56%
“…The US-Mexico border has been considered an obesogenic region. 6 Factors that contribute to an obesogenic environment include lack of time, physical pain, depression, being overweight, unsafe neighborhoods, lack of facilities for exercise, 6,29-32 a lower socioeconomic class that experiences poor availability and barriers to accessing high quality reasonably priced foods, 6 and the increased availability of affordable and well-marketed processed high-caloric and high-fat foods. 33…”
Section: Discussionmentioning
confidence: 99%